2020
DOI: 10.1093/ejcts/ezz348
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up outcomes after the frozen elephant trunk technique in chronic type B dissection

Abstract: OBJECTIVES Our goal was to present our experience with a hybrid approach to the frozen elephant trunk (FET) technique for the treatment of patients with chronic type B aortic dissection. METHODS Between January 2013 and July 2019, 86 patients underwent the FET procedure at our centre. In 20 patients, the indication was chronic type B aortic dissection with a concomitant proximal aortic lesion. We evaluated the sites of proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The early and long-term results of this technique for patients with chronic type B or non-A non-B AD were acceptable, which indicates that the FET procedure is a safe and effective approach for such patients. The competing analysis showed that the need for distal aortic reintervention was 13.0% at 7 years, which was comparable with the result reported by Charchyan et al ( 20 ). The authors showed that the cumulative incidence rates of aortic reintervention were 5.6% at 0.5 years and 11.1% at 4 years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The early and long-term results of this technique for patients with chronic type B or non-A non-B AD were acceptable, which indicates that the FET procedure is a safe and effective approach for such patients. The competing analysis showed that the need for distal aortic reintervention was 13.0% at 7 years, which was comparable with the result reported by Charchyan et al ( 20 ). The authors showed that the cumulative incidence rates of aortic reintervention were 5.6% at 0.5 years and 11.1% at 4 years.…”
Section: Discussionsupporting
confidence: 88%
“…We recommend that the FET procedure be performed if the patients have type B or non-A non-B AD concomitant with the following conditions ( 20 ): (i) aortic root or ascending aorta aneurysm; (ii) left common carotid artery dissection involvement or aortic arch aneurysm; (iii) proximal aortic lesion with coronary artery disease or aortic valve disease; (iv) contraindication for TEVAR; and (v) a high risk of RTAAD. The FET procedure for treating type B or non-A non-B AD unfit for TEVAR has some advantages ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In selected cases of difficult aortic arch anatomy and risk for retrograde type A dissection after TEVAR, a frozen elephant trunk can be an alternative method for arch repair [29]. Sometimes, when the aortoiliac segment is not suitable for inflow, antegrade visceral debranching from the ascending aorta might be performed [30].…”
Section: Discussionmentioning
confidence: 99%
“…Of 64 studies reporting outcomes of patients included in this report 13–76 . The proportions of studies from Asia, Europe, and North America were 54.7%, 31.3%, and 10.9%, respectively.…”
Section: Methodsmentioning
confidence: 99%